Designer's guide to Eurocode 1 actions on bridges : EN 1991-2, EN 1991-1-1, -1-3 to -1-7 and EN 1990 annex A2 - Calgaro, J.-A (Designers' guides to the eurocodes, 2010)
This series of Designers Guides to the Eurocodes provides comprehensive guidance in the form of design aids, indications for the most convenient design procedures and worked examples. The books also include background information to aid the designer in understanding the reasoning behind and the objectives of the codes. All of the individual guides work in conjunction with the Designers Guide to EN 1990 Eurocode: Basis of Structural Design.